Digital Pacer Detection in Diagnostic Grade ECG - Zarar, Shuayb; Garudadri, Harinath (IEEE Int. Conf. E-Health Networking Applications and Services (Healthcomm), 2011)
Pulses from a cardiac pacemaker appear as extremely narrow and low- amplitude spikes in an ECG. These get misinterpreted for R-peaks by QRS detectors, leading to subsequent faulty analysis of several algorithms which rely on beat-segmentation. Detection of the pacer pulses, thus, necessitates sampling the ECG signal at high data rates of 4-16 kHz. In a wireless body sensor network, transmission of this high-bandwidth data to a processing gateway, for pacer detection, is extremely power consuming. In this paper, we describe a compressed sensing approach, which enables reliable detection of AAMI/EC11 specified pacer pulses using ECG data rates of 50-100 sps, an order of magnitude smaller than those used in typical detection algorithms in the literature.
Best-paper Award Nomination